If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 16 = -13x + 3 Reorder the terms: 16 = 3 + -13x Solving 16 = 3 + -13x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '13x' to each side of the equation. 16 + 13x = 3 + -13x + 13x Combine like terms: -13x + 13x = 0 16 + 13x = 3 + 0 16 + 13x = 3 Add '-16' to each side of the equation. 16 + -16 + 13x = 3 + -16 Combine like terms: 16 + -16 = 0 0 + 13x = 3 + -16 13x = 3 + -16 Combine like terms: 3 + -16 = -13 13x = -13 Divide each side by '13'. x = -1 Simplifying x = -1
| 5x+20=5x-10 | | 4a^2+27a+35=0 | | 45-[4-2y-4(y+7)]=-4(1+3y)-[4-3(y+2)-2(2y-5)] | | 12x+2=4(2x+1)-x+6 | | 3t^2+26t+48=0 | | 6n(n+7)= | | p^2-5p-36=0 | | 3v(7v+4)=0 | | 14-8X=124-43X | | 14=3x-4 | | 126-5x=5x+16 | | 5(m+2)-2=6m-9 | | 4x^4=13x^2+9 | | -(4y+1)-(-3y-5)=4 | | 11x(27)(2x)=246 | | 6x+11=101-3x | | 8x+7=88-x | | 6x+z=13 | | 8x+7=88-7 | | -8x+5=29 | | 8(2x-2)=2(8x+4) | | 4N-12=20 | | 1052=16x^2 | | 8x^2=32 | | 36x^2=1 | | (N+5)*10=90 | | 9(4x-5)=3(12x+7) | | x^2+45=0 | | 4+7m-1=7m+9-3m | | 3(a+4)=5(a-6) | | (N-7)*4=40 | | 10(3h+2)= |